Towards Eco-neighborhoods, solutions for sustainable development, construction and energy saving technologies - Omar, Osama (Journal of Architecture and Urbanism, 2018)
Global interest in the concept of sustainability has prompted the swift and extensive developments of green technologies, products, competitions, organizations, and resources. As evidenced by international environmental agreements and conferences held that aim to resolve global warming such as the 2009 UN Climate Change Conference in Copenhagen, the world is becoming focused on sustainable policies and practices (Tibi, Ghaddar, & Ghali, 2012). This research will address the urban problems in present in Arab countries including environmental pollution and the evident social problems like disintegration and isolation by studying the three zones of Mar Mikhael, Arab el-Maslakh, and Nour Hajin which are known to be economically unequal. The methodology of this research is based on the analytical study of the three interdependent components of sustainable development and design which are society/people, the environment, and economics applying on each case study. This paper will identify solutions relative to environmental, technological, energy saving, as well as sustainable and green buildings in urban design. Some of the remaining solutions target solving environmental pollution and social problems. Others target to improve the quality of the economic level of the neighborhood. The result of this research will a number of recommendations on several levels (Governmental level, Local NGOs). Another type of results will be as architectural design solution for environmental issue and urban problems based on data collection of case study at several items by team of students attending in local competition of urban design.